Molecular biology : a very short introduction - Divan, Aysha; Royds, Janice (Oxford, United Kingdom : Oxford University Press, 2016)
Molecular Biology is the story of the molecules of life, their relationships, and how these interactions are controlled. It is an expanding field in life sciences, and its applications are wide and growing. We can now harness the power of molecular biology to treat diseases, solve crimes, map human history, and produce genetically modified organisms and crops, and these applications have sparked a multitude of fascinating legal and ethical debates. In this Very Short Introduction, Aysha Divan and Janice Royds examine the history, present, and future of Molecular Biology. Starting with the building blocks established by Darwin, Wallace and Mendel, and the discovery of the structure of DNA in 1953, they consider the wide range of applications for Molecular Biology today, including the development of new drugs, and forensic science. They also look forward to two key areas of evolving research such as personalized medicine and synthetic biology. --
The early milestones -- DNA -- RNA -- Proteins -- Molecular interactions -- Genetic engineering -- Molecular biology in the clinic -- Molecular forensics -- Future challenges -- References -- Further reading
Includes bibliographical references (pages 139-140) and index.
Keywords: Molecular biology; Molecular Biology; Molecular biology